(untitled) (Journal of Science and Technology, 2016)
Hypotensive activities of the alcoholic extract of T. tetraptera fruits have been earlier demonstrated in cats, rats and rabbits. In the present study, we demonstrate myorelaxant actions of the extract in isolated smooth muscle preparations. Relaxations were dose-dependent: EC50s were 0.3 ± 0.01, 2.4 ± 0.1 and 4.3 ± 0.01 mg/ml for rat anococcygeus, rat uterus and guinea-pig taenia coli respectively. Also, spasmogenic actions of noradrenaline, carbachol, Ca2+ and K+ in the rat anococcygeus and uterus were all suppressed by the extract. The effect of the extract on Ca2+-induced contractions were investigated in guinea-pig isolated taenia coli and atria preparations and compared to nifedipine, a calcium- channel blocker . Pre-treatment with T. tetraptera (1-10 mg/ml) and nifedipine (0.01-0.1 μg/ml) for 15 minutes in Ca2+-free K+ (100 mM) medium caused a right ward shift of the concentrationresponse curves for CaCl2-induced contractions in atria and taenia coli with depressed maximal response, suggestive of a non-competitive interaction. In all tissues investigated, the extract nonspecifically reduced both the natural tone and agonist-induced contractions. Thus smooth muscle relaxant actions of the extract may partly account for the hypotensive actions of T. tetraptera fruits.